ORGANIC ANIONS PRODUCTION BY BACILLUS SP. TO ENHANCE MAIZE AND MILLET GROWTH - N. Khan; R. Batool; N. Jamil (Journal of Animal and Plant Sciences, 2017)
In this study, four bacterial isolates, YIId (KT764030), YIC (KT764029), S2 (KT764028) and O2 (KT764027) were selected on the basis of their broad range Zinc Oxide and Zinc Phosphate solubilising and antimicrobial activity against indicator bacterial strains. All four isolates were able to solubilise Zinc Phosphate and Zinc Oxide. The solubilisation activity is mostly related to the production of organic anions, so the production of Gluconic acid was confirmed by HPLC. Plant growth experiments were performed and the findings revealed very promising results from selected bacterial isolates YIC and YIId. The Maize seedlings showed 51% increase in seedling length, when treated with bacterial isolate YIC. The maximum increase approximately 39% and 36% in Millet seedling length was recorded as compared to the control when treated with bacterial isolate YIC, Zinc oxide and bacterial isolate YIId, zinc oxide and zinc phosphate, respectively. The result showed an increase in seedling biomass. Millet plants showed maximum soluble protein content (357.7 µg ml-1) when treated with YIC, ZnO and Zn3(PO4)2 as compared to control (99.8 µg ml-1).  The free proline content of Maize plants was significantly increased when inoculated with bacterial isolate YIId (562.68 µg ml-1) as compared to control (316.52 µg ml-1). It was concluded that selected PGPR can be used to enhance plant yield and biomass by producing organic anions to solubilize zinc and phosphate salts.
Keywords: Zinc Solubilisation; HPLC; Gluconic acid; Plant Growth Promoting Bacteria; Proline